Florística e fitossociologia em parcelas permanentes da Mata Atlântica do sudeste do Brasil ao longo de um gradiente altitudinal - Joly, Carlos Alfredo; Assis, Marco Antonio [UNESP]; Bernacci, Luis Carlos; Tamashiro, Jorge Yoshio; de Campos, Mariana Cruz Rodrigues; Gomes, José Ataliba Mantelli Aboin; Lacerda, Maryland Sanchez; dos Santos, Flávio Antonio Mães; Pedroni, Fernando; Pereira, Larissa de Souza; Padgurschi, Maíra de Campos Gorgulho; Prata, Eduardo Magalhães Borges [UNESP]; et al. (My University, 2012)
This paper summarizes floristic and phytossociology data of 11, out of 14 plots of 1 ha, allocated along an altitudinal gradient in the Serra do Mar, São Paulo, Brazil. The study was conducted at Serra do Mar State Park and the plots start at the sea level (10 m - plot of Restinga Forest that occurs at Praia da Fazenda, Picinguaba, municipality of Ubatuba) up to 1100 m above sea level (the Montane Ombrophilous Dense occurs alongside the Itamambuca Trail, municipality of São Luis do Paraitinga). The Restinga Forest occurs in Pleistocenic Coastal Plain where the soil is classified as a sandy Quartzipsamment (Quartzenic Neosol), while along the slopes of the Serra do Mar, the Ombrophylus Dense Forest grows on the top of a pre-Cambrian crystalline basement with granitic rocks, where the soil is a sandy-loam Dystrophic Inceptisol (Cambisol/Latosol). In all 14 plots soils are acidic (pH 3 - 4), chemically poor, with high dilution of nutrients and high saturation of aluminum. In the Restinga and at the foot of the slope the climate is Tropical/Subtropical Humid (Af/Cfa), with no dry season, an average annual rainfall over 2,200 mm and an average annual temperature of 22 °C. Towards the top of the Serra do Mar there is a gradual cooling along the slope, but there is no reduction in rainfall, so at 1,100 m above sea level the climate is classified as Humid Subtropical (Cfa/Cfb), with no dry season and an average annual temperature of 17 °C. It is important to remark that, almost daily, from 400 m above sea level up to the top of slopes the mountains are covered by a dense fog. In the 14 plots 21,733 individuals with DBH ≥ 4.8 cm, including trees, palms and ferns, were marked, measured and sampled. The average number of individuals sampled in each plot was 1264 ind.ha-1(± 218 SE 95%). Within the parameters considered trees prevailed (71%in the Montane ODF to 90% in the Restinga Forest), followed by palms (10% in the RF and 25% in the Montane Ombrophilous Dense Forest/ODF) and ferns (0% % in the RF and 4% in the Montane ODF). Regarding these proportions the Exploited Lowlands ODF differs from the others with only 1.8% of palm trees and striking 10% of ferns. The forest canopy is irregular with heights ranging from 7 to 9 m, rarely emergent trees reach 18 m, and due to this irregularity of the canopy the amount of light that gets through sets conditions for the development of hundreds of epiphytic species. Aside from Montana ODF, where the number of dead trees was more than 5% of individuals sampled, in the other phytophysiognomies this value was below 2.5%. In the 11 plots where the floristic study was conducted we found 562 species in 195 genera and 68 families. Only seven species - Euterpe edulis Mart. (Arecaceae), Calyptranthes lucida Mart. ex DC. and Marlierea tomentosa Cambess (both Myrtaceae), Guapira opposita (Vell.) Reitz (Nyctaginaceae), Cupania oblongifolia Mart. (Sapindaceae), Cecropia glaziovii Snethl. and Coussapoa microcarpa (Schott) Rizzini (both Urticaceae) - occurred from Restinga to Montane ODF, while 12 other species did not occur only in the Restinga Forest. Families with the greatest number of species are Myrtaceae (133 spp), Fabaceae (47 spp), Rubiaceae (49) and Lauraceae (49) throughout the gradient and Monimiaceae (21) specifically in portions Montane ODF. Only in the F plot, where logging has occurred between 1950 and 1985, the abundance of palm trees has been replaced by Cyatheaceae. The study shows a peak of diversity and richness, Shannon-Weiner index (H') ranging from 3.96 to 4.48 nats.ind-1, in the intermediate altitudes (300 to 400 m) along the slope. Several explanations for thishytophysiognomies of the Atlantic ODF due to climate fluctuations during the Pleistocene. The results presented in this paper d result are raised here, including the fact that these elevations are within the limits expansions and retractions of the different pemonstrate the extraordinary richness of tree species of the Atlantic Rainforest from the northeastern coast of the State of Sao Paulo, reinforcing the importance of its conservation throughout the altitudinal gradient. The richness of this forest justifies a long term commitment to study its dynamics and functioning through permanent plots, and monitor the impacts of climate change in this vegetation.
Floristic and phytosociology in permanent plots of the Atlantic Rainforest along an altitudinal gradient in southeastern Brazil
Keywords: BIOTA Functional Gradient Project; Nucleo Picinguaba; Nucleo Santa Virginia; Phytophysiognomies; Serra do Mar State Park; Species richness; Vegetation Classification System